Theoretical insights to elastic and thermal properties of WB4 tetraborides: A first-principles calculation. (February 2022) - Wang, Yong; Wu, Ying; Lu, Yaoping; Wang, Xinyu; Duan, Yonghua; Peng, Mingjun
Abstract: As an efficient tool for theoretical investigation, the first-principles calculation based on Density Functional Theory (DFT) has been applied to various fields of material development. In the present work, the first-principles calculation has been employed to predict the mechanic characteristics and thermal performances of three novel WB4 tetraborides. The single crystal constant C ij calculated by the stress-strain method shows that hP 10-WB4 and hR 15-WB4 tetraborides have stable crystal structures and elastic anisotropies. However, the calculated phonon dispersions reveal that hP 20-WB4 is dynamically unstable. According to the calculated elastic modulus and anisotropy indexes A, the sequence of elastic anisotropy is hP 10-WB4 < hR 15-WB4 . Besides, the Debye temperature of WB4 has such a sequence: hP 10(737.042K) > hR 15(640.517K), and the sound velocities have great anisotropy. Moreover, the calculated k min shows the strong anisotropy and their values show the order: hP 10 > hR 15 . Highlights: The hP10 and hR15-WB4 have stable crystal structures and elastic anisotropies. The hP 10-WB4 has the larger hardness (29.0 Gpa) than hR15-WB4 The hP 10-WB4 has a brittle nature while hR 15-WB4 are ductile. The sequence of elastic anisotropy is hP 10-WB4 < hR 15-WB4 . The Debye temperature has such order: hP 10(737.042 K)> hR 15(640.517 K).